The Effects of Product Quality, Service Quality, and Café Atmosphere on Purchase Decisions: Evidence from a Local Coffee Shop in Indonesia - Rami Irna Putri; Tri Citra Aulia Sukma; Susi Indriyani (CV. Media Digital Publikasi Indonesia, 2026)
The rapid growth of coffee shop businesses in urban Indonesia has intensified competition and shifted consumer expectations toward both functional and experiential value. This study examines the effects of product quality, service quality, and café atmosphere on consumer purchase decisions at a local coffee shop in Bandar Lampung. A quantitative explanatory approach was employed using survey data collected from 98 customers who had purchased at least twice. Data were analyzed using multiple linear regression with SPSS. The results reveal that product quality and service quality have positive and statistically significant effects on purchase decisions, while café atmosphere does not show a significant partial effect. However, all three variables jointly exert a significant influence on purchase decisions, explaining 65.1% of the variance. These findings indicate that functional and relational attributes dominate consumer decision-making in local coffee shop contexts, whereas experiential factors play a complementary role. The study contributes to consumer behavior literature by refining the role of café atmosphere as a boundary condition and provides managerial insights for local café operators in emerging urban markets.